Impairment of a membrane-targeting protein translated from a downstream gene of a “self-cleaving” T2A peptide conjunction - Sudarat Hadpech (2018)
© 2018 Elsevier Inc. The requirement for reliable bicistronic or multicistronic vectors in gene delivery systems is at the forefront of bio/biomedical technology. A method that provides an efficient co-expression of multiple heterologous proteins would be valuable for many applications, especially in medical science for treating various types of disease. In this study, we designed and constructed a bicistronic expression vector using a self-cleaving 2A peptide derived from a virus of the insect Thosea asigna (T2A). This exhibited the most efficient cleavage of the 2A sequence. Two versions of the T2A-based vector were constructed by switching the DNA sequences encoding the proteins of interest, the N-myristoylated protein and the nuclear-homing protein, upstream and downstream of the 2A linker, respectively. Our results showed that similar levels of mRNA expression were found and 100% of cleavage efficiency of T2A was observed. Nevertheless, we also reported the cleared evidence that the N-myristoylated protein cannot be placed downstream of the 2A sequence. Since the protein product fails to translocate to the plasma membrane due to altered myristoylation process, the gene position of the T2A-based vector is meaningful for the subcellular localization of the N-myristoylated protein. Therefore, the observation was marked as a precaution for using the 2A peptide. To adopt the 2A peptide technology for generating the bicistronic or multicistronic expression, the vector design should be carefully considered for the transgene position, signal sequences, and post-translational modifications of each individual protein.